2016
DOI: 10.1111/jbi.12860
|View full text |Cite
|
Sign up to set email alerts
|

Evolution in the South American ‘Lost World’: insights from multilocus phylogeography of stefanias (Anura, Hemiphractidae, Stefania)

Abstract: Aim To investigate the influence of tepuian geomorphology on species diversification in the Pantepui biogeographical region based on the phylogenetic relationships and divergence times of tepui‐endemic clades of stefania frogs (Stefania, Hemiphractidae). Location The ‘tepuis’ and uplands/lowlands of the Pantepui biogeographical region of northern South America, one of the least accessible and least studied areas in the world. Methods Two mitochondrial and two nuclear DNA sequences from 60 individuals of Stefan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
60
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(65 citation statements)
references
References 43 publications
5
60
0
Order By: Relevance
“…Based on a rate of mitochondrial sequence divergence of approximately 1% per million years, this would provide an age estimate of 1.5 Myr for the divergence of upland G. carapo from nearby lowland populations. This suggests that G. carapo is a more recent addition to the fauna of upland Guiana, in line with ages of some amphibians found on tepui summits (Kok et al, 2012(Kok et al, , 2016. Based on these results, we suggest that upland Guianas ichthyofauna consist of a mosaic of relatively ancient endemics combined with more recent arrivals like G. carapo.…”
Section: Biogeographical Relationships Between Upland and Lowland Gsupporting
confidence: 74%
“…Based on a rate of mitochondrial sequence divergence of approximately 1% per million years, this would provide an age estimate of 1.5 Myr for the divergence of upland G. carapo from nearby lowland populations. This suggests that G. carapo is a more recent addition to the fauna of upland Guiana, in line with ages of some amphibians found on tepui summits (Kok et al, 2012(Kok et al, , 2016. Based on these results, we suggest that upland Guianas ichthyofauna consist of a mosaic of relatively ancient endemics combined with more recent arrivals like G. carapo.…”
Section: Biogeographical Relationships Between Upland and Lowland Gsupporting
confidence: 74%
“…(), Skeels and Cardillo () and Kok et al. (). The application of model selection in these cases appears to be motivated by the same reasons one selects among models of nucleotide evolution for phylogeny reconstruction: that the best‐fit model is necessary for accurate inferences.…”
Section: Introductionmentioning
confidence: 99%
“…For simple inference of ancestral ranges on a fixed phylogeny, a DEC-based model may be defensible if statistical model selection is not used to justify the choice, and it is understood that inferences about cladogenetic range inheritance lack any relation to time, normally a fundamental axis of evolutionary models. et al (2016), Givnish et al (2016), Skeels and Cardillo (2017) and Kok et al (2017). The application of model selection in these cases appears to be motivated by the same reasons one selects among models of nucleotide evolution for phylogeny reconstruction: that the best-fit model is necessary for accurate inferences.This trend is unfortunate for two reasons: first, DEC+J is a poor model of founder event speciation, and second, unlike nucleotide models, DEC and DEC+J cannot be compared using standard…”
mentioning
confidence: 99%
“…The application of molecular genetics and its integration into taxonomic research on anurans has revealed a tremendous amount of hidden diversity, particularly in the most species-rich tropical regions (e.g., Köhler et al 2005a;Stuart et al 2006;Fouquet et al 2007;Crawford et al 2010Crawford et al , 2013Funk et al 2012;Barej et al 2015;Kok et al 2017). A great part of this uncovered diversity is considered to represent different species (Fouquet et al 2007;Vieites et al 2009).…”
Section: Dna Barcodingmentioning
confidence: 99%